PREDICTIVE VALUES OF PROCALCITONIN FOR SECONDARY BACTERIAL INFECTIONS IN PATIENTS WITH COVID-19 - Ergashov Maqsudjon Muzaffarovich (TADQIQOTLAR, 2025)
ANNOTATION. This article highlights the importance of C-reactive protein (CRP) and procalcitonin (PCT), and cytokines in determining the prognosis of SARS- CoV-2-associated pneumonia. The article discusses the methods used to measure these biomarkers and the results of studies that have investigated their use in predicting the severity and outcome of SARS-CoV-2-associated pneumonia. The article concludes with a discussion of the implications of these findings and suggestions for future research.